Influence of age on static postural control in adults with type 2 diabetes mellitus: a cross-sectional study - Zhuang, Yujun; Hong, Zhenzhen; Wu, Lijuan; Zou, Chunyan; Zheng, Yan; Chen, Liming; Yin, Lianhua; Qin, Jiawei (Frontiers in Endocrinology, 2023)
Aim: The objective of this study was to determine the static postural control characteristics assessed by a force platform in Type 2 diabetes mellitus (T2D) with different age groups. This study also explored the relationship of the age and static postural control parameters Methods: A total of 706 participants with T2D were included in this study. The participants were stratified into three groups by age: Group 1 (< 60 years), Group 2 (60-70 years), and Group 3 (>70 years). All participants performed two-legged static stance postural control assessment on a firm force platform. The Center of Pressure (CoP) parameters were collected under eyes-open and eyes-closed conditions. Kruskal–Wallis tests were used to determine the difference among the different age groups. Multivariate regression analysis was performed to examine the relation between age and static postural control parameters. Results: Group 1 (<60 years) had significantly less total track length (TTL), sway area (SA), and velocity of CoP displacements in Y direction (V-Y) under both eyes-open and eyes-closed conditions compared with Group 2 (60-70 years) and Group 3 (>70 years). Group 1 (<60 years) had significantly less maximum sway length of CoP along X direction (MSL_X) and more track length per unit area (TTL/SA) under eyes-open condition compared with Group 2 (60-70 years) and Group 3 (>70 years). There were significantly positive correlations between age and the most static postural balance parameters (TTL, SA, MSL-X, MSL-Y, and V-Y). There were significantly negative correlations between age and TTL/SA. Conclusion: This study suggested that older T2D patients had worse static postural control performance compared with those younger T2D patients. Most static postural control parameters presented significant correlation with age, the older age, the worse static postural control.